(untitled) (Journal of Medicine, 2019)
Background: A large number of kala-azar cases from a particular village in Debigonj upazila of Panchaghar, a remote district of Bangladesh, led us to carry out the study of the situation. Materials & methods: This cross-sectional study was done among clinically screened people at the health camp in two days in Dararhat in Debigonj upazila of Panchaghar. Results: Around 700 people were screened at the health camp and 51 (7.2%) were suspected to have either Kala-azar or related disorders where 42 (82%) were rk-39 test positive. The disease was more prevalent among adult (59.6%) and children (23.8%) under the age of 10 years. However, there was no clear linear relationship between the prevalence of the disease and age group. Kala-azar occurred in both male and female, and its prevalence did not correlate significantly with income. A history of fever (73.8%) and splenomegaly (45.2%) was noted in most of the kala-azar cases. A significant number of PKDL (26.2%) cases were also found in that area. Conclusions: Since there are a significant proportion of PKDL cases, eradication will be very tough unless the health authority take adequate measure to identify and treat them properly. J MEDICINE JUL 2019; 20 (1) : 25-28